Metacognitive Strategies Used by EFL Listeners: A Student Need Analysis in Developing Listening Tasks - Arum Nisma Wulanjani; Lilia Indriani (Metathesis: Journal of English Language, Literature, and Teaching, 2019)
Listening has been claimed as one of the most challenging skill to teach since many research found that the students, especially EFL students, still worried when having a listening  class. Listening still gives a fear for the students as long as they couldn’t deal with their worriness in joining listening class. It may be caused by their nescience in figuring out what strategy they could use while they are trying to do listening tasks given.This study aims to investigate metacognitive listening strategies used by EFL students in listening class. This study is to find out what strategies mostly adopted by the students in listening class. Besides, this study also tries to propose a need mapping for constructing listening tasks. The students were English Departmenet students of Universitas Tidar. In this study, the data were collected by using Metacognitive Awareness Listening Questionnaire (MALQ) adopted form Vandegrift. The results revealed that the students mostly used problem-solving strategies while doing listening tasks. The use of this strategy implies that most of the students belong to effective listeners. On the other hand, the use of mental translation is the least use among the students. These results are needed  as one of the basic needs in developing listening tasks. The result could give a clear guidance and limitation for developing listening tasks for the students.